KAJIAN SEMIOTIKA ROLAND BARTHES PADA CERPEN TAMU KARYA BUDI DARMA - Deva Monanda; Liza Septa Wilyanti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research was conducted using a semiotic code study. The focus of semiotics used in this study is based on the concept of Roland Barthes, with the aim of knowing the codes in the short story Tamu by Budi Darma. This research was conducted using a qualitative descriptive method in literary works, namely the short story Tamu by Budi Darma in analyzing it. While the reading technique was used for data collection used by researchers, besides that note-taking techniques were also used in the research conducted. while the data analysis technique used in this research is to use descriptive analysis method. The results of the analysis of this research are the codes in the semiotics of Roland Barthes' concept, namely the hermeneutic code, connotation code, symbolic code, action code, and cultural code. The 10 data consist of 3 hermenuetic codes, 1 connotation code, 3 symbolic codes, 2 action codes and 1 cultural code.